2016
DOI: 10.1152/ajplung.00043.2016
|View full text |Cite
|
Sign up to set email alerts
|

Nur77 attenuates endothelin-1 expression via downregulation of NF-κB and p38 MAPK in A549 cells and in an ARDS rat model

Abstract: Acute respiratory distress syndrome (ARDS) is characterized by inflammatory injury to the alveolar and capillary barriers that results in impaired gas exchange and severe acute respiratory failure. Nuclear orphan receptor Nur77 has emerged as a regulator of gene expression in inflammation, and its role in the pathogenesis of ARDS is not clear. The objective of this study is to investigate the potential role of Nur77 and its underlying mechanism in the regulation of endothelin-1 (ET-1) expression in lipopolysac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 99 publications
(109 reference statements)
1
29
0
Order By: Relevance
“…The sirtuin 1 (SIRT1) protein was the first member of the Sirtuin protein family to be discovered (5). It has been reported that enzymes associated with SIRT1 are class III histone acetylation enzymes dependent on nicotinamide adenine dinucleotide (NAD + ), which is highly conserved (6).…”
Section: Introductionmentioning
confidence: 99%
“…The sirtuin 1 (SIRT1) protein was the first member of the Sirtuin protein family to be discovered (5). It has been reported that enzymes associated with SIRT1 are class III histone acetylation enzymes dependent on nicotinamide adenine dinucleotide (NAD + ), which is highly conserved (6).…”
Section: Introductionmentioning
confidence: 99%
“…Nur77 deficiency exacerbated OVA-induced allergic airway inflammation in mice [26]. Also, Nur77 expression limited LPS-induced inflammation and tissue damage in a rat model of acute respiratory distress syndrome [27]. Nur77 was identified as a potential modulator of pulmonary arterial hypertension, as its expression was downregulated in lungs of patients with pulmonary arterial hypertension and also in cultured pulmonary microvascular endothelial cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…Mitogen-activated protein kinase (MAPK) signal MAPK signaling is suppressed by blocking the phosphorylation of JNK and p38, which decreases the levels of the pro-inflammatory cytokines IL-6 and TNF-α and increases the level of the anti-inflammatory cytokine IL-10 to subsequently alleviate the inflammation in subjects with sepsis-induced ARDS [54].…”
Section: Jun N-terminal Kinase (Jnk) and P38mentioning
confidence: 99%
“…At the transcriptional level, several studies have postulated an interaction between the nuclear orphan receptor and endothelin-1 (ET-1). As a negative regulator, Nur77 is activated by cytosporone B (CsnB) and suppresses ET-1 expression by decreasing the lipopolysaccharide (LPS)-induced phosphorylation of NF-κβ p65 and p38 MAPK, which relieved lung injury in a mouse model of ARDS [54]. Furthermore, in vascular endothelial cells, 6-mercaptopurine (6-MP) also activates Nur77and subsequently decreases ET-1 expression by inhibiting AP-1-dependent c-Jun promoter activity [55].…”
Section: Lincrna-p21mentioning
confidence: 99%